(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
Ants have an important ecological role and they can help in prevention and pests management. That is why is important to know the species and understand the function they perform in different systems. The main propose of this work was to study the ants diversity on the ground in Citrus sinensis crop, with irrigation (IC) and without (NC). Pitfall traps, foliage patterns, manual capture and sifting litter were used to characterize ant assemblages and compare the ant diversity between treatments. In total, 26 species and 13 genera were collected, grouped in 5 families. The irrigated crop presented the higher richness, abundance and diversity index values, although the differences between crops were not significant. Nine ant guilds were recognized, distributed in three groups (epigeas, arboreal and hypogea). The epigeous ant group was the one that presented the most abundance in both crops. In the two treatments the three general groups were found, even though in NC crop, the Specialist predators (Sp) and Agile pseudomyrmicinae (Ap) guilds were not registered, which were exclusives of treatment CR. Sf index showed big functional similarity between both treatments. This study provides four new species records for Corrientes province: Cephalotes bruchi, Cephalotes minutus, Cyphomyrmex transversus y Pheidole jelskii.